Is Aerated Soft Drink and Packaged Juice Consumption an Independent Risk Factor to Cause Non-Alcoholic Fatty Liver Disease - Kunal, Kukreja; Prateek, Kinra; MS, Tevatia (Annals of Pathology and Laboratory Medicine, 2020)
BACKGROUND: There has been an increase in consumption of aerated sweetened soft drinks and packaged juices high in carbohydrates/fructose by humans across the globe. There have been various studies with contradictory inferences of association of chronic sweetened soft drink (rich in high fructose corn syrup) intake and NAFLD. This study was undertaken with the aim to determine the quantity, frequency, duration and type of sweet soft drinks /packaged fruit juices consumption in patients with NAFLD as compared to that in control population. Other objectives included assessment of the independent role of sweetened soft drinks as a risk factor for NAFLD in the absence of metabolic syndrome and to correlate the level of steatosis (objectively graded by ultrasonography) with the amount of intake of soft drinks in patients of NAFLD. METHOD : 50 patients of NAFLD as diagnosed clinically and by ultrasonography were identified and compared with 50 age matched control population reporting to the hospital with ailments other than NAFLD. The presence or absence of metabolic syndrome was noted in all the patients. The history of soft drink intake was obtained from the patient under following heads: a) quantity consumed, b) type of soft drink/packaged juice consumed, c) period of ingestion and d) frequency of consumption. RESULT : The average monthly consumption, duration of consumption and the mean total sugar consumption of sweetened soft drinks / packaged juices were significantly higher in patients with NAFLD versus those in the control group (p=0.0002; <0.0001; p=0.002 respectively). The quantity and chronicity of intake correlated well with the grade of NAFLD. As the average monthly consumption and mean sugar consumption increased the grade of fatty liver on USG also increased (p= 0.004). A total of 11 patients out of all the 100 patients (study and control groups combined) had a daily intake of 150-300ml of SSD for a period ranging from 5 to 20 years. Two of these had grade I NAFLD whereas 9 had grade II-III NAFLD. Five of these 11 patients had a daily intake of 250ml or greater. All these 5 patients had grade II-III NAFLD documented on ultrasound findings. Conclusion The consumption of sweetened soft drinks and packaged juice is on the rise in India. The intake of these drinks is significantly higher in patients with NAFLD.